El despojo de la riqueza biológica - Rodríguez Cervantes, Silvia (Editorial Universidad Nacional (EUNA), 2013)
This book outlines the historical antecedents of genetic erosion by monocultures and other predatory activities promoted by transnational corporations; the responses to this problem and the analysis of various international treaties that promote the aggressive expansion of such corporations.